Wölfflin and Landscape History: "Painterly, " "Linear" and the Mannerist Garden. Issue 2 (3rd May 2020) - Morgan, Luke
Abstract: This article examines Heinrich Wölfflin's discussion of sixteenth-century Italian landscape design in Renaissance and Baroque (1888). It argues that Wölfflin's interpretation influenced twentieth-century accounts of the mannerist garden, from Luigi Dami's Il giardino italiano (1924) and the Fascist-era Mostra del giardino italiano (1931), to later Anglo-American scholarship. Close attention is paid to a curious paradox at the heart of Wölfflin's account of gardens, namely that, as he himself acknowledges: "It must seem strange that landscape, the most painterly of all subjects, should be the most rigorously subordinated to architectural rules in the period of the 'painterly' style." The article proposes that Wölfflin's categories of "painterly" and "linear" are constitutive of an interdependent or dialectical relationship, and that this premise may have heuristic potential for an alternative history of the early modern garden.